SIMULATION OF HOT WATER INJECTION AS AN ALTERNATIVE FOR HANDLING MINE WASTEWATER AT PT XYZ - Susanto, Edy
Protecting the environment is an important commitment for mining companies in running their business, one of which is ensuring that wastewater from mining activities meets environmental quality standard in accordance with applicable regulation. PT XYZ is a gold mining company operating on Sulawesi Island. The mining area is in a volcanoc area which is a geothermal prospect area. One of the mining pits (Pit A) has hot water coming out with a temperature of >70oC and a discharge of up to 1000 liters/second. The hot water comes out becomes wastewater which cannot be directly released into water bodies because it does not meet quality standards. The mine wastewater must be treated to reduce the levels of arsenic, boron, chloride, total dissolved solid (TDS) and temperature if it is to be released into a nearby river, while release into the sea only requires a decrease in temperature. Another option is to return this wastewater to groundwater flow by injection. The treatment currently carried out uses the mixing pond and cooling circuit method before being released into the sea. The methods require a large area to provide infrastructure, while mining also requires land expansion. As mining progresses, the mine openings become larger and the discharge of water that comes out will be greater, so injection needs to be considered. This study was carried out to get an estimate of the hot water discharge that will come out as the mine openings become larger and an initial picture of the location that will be targeted for injection. From the field test data that has been carried out previously, calculation and simulations using the finite difference method with the help of MODFLOW software, it is obtained that the estimated water discharge can reach 2000 liters/second and the recommended injection location is on the north side of Pit A with a minimum distance of 2 km from the final pit design. It is hoped that the results of this research can be used as a reference for further research before this injection is chosen and implemented.